2014
DOI: 10.1002/ange.201406099
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Residue‐Specific Dopa‐Incorporated Engineered Mussel Bioglue with Enhanced Adhesion and Water Resistance

Abstract: Misaminoacylation of 3,4‐dihydroxyphenylalanine (Dopa) molecules to tRNATyr by endogenous tyrosyl‐tRNA synthetase allowed the quantitative replacement of tyrosine residues with a yield of over 90 % by an in vivo residue‐specific incorporation strategy, to create, for the first time, engineered mussel adhesive proteins (MAPs) in Escherichia coli with a very high Dopa content, close to that of natural MAPs. The Dopa‐incorporated MAPs exhibited a superior surface adhesion and water resistance ability by assistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 39 publications
5
41
0
Order By: Relevance
“…[16] However, most approaches suffer from lowh ydroxylation efficiencya nd specificity or low protein yields. [17] Residue-specific replacement [18,19] of Tyrb yD OPA, exploiting the substrate promiscuityo fEscherichia coli tyrosyl-tRNA synthetase (EcTyrRS), has been reported for MAP types 3a nd 5, [17] but is limited by the poor activation of DOPAb yEcTyrRS, accompanied by Tyr incorporation ( Figure S1 in the Supporting Information), and impaired cell growth due to proteome-wide DOPAi ncorporation.…”
mentioning
confidence: 99%
“…[16] However, most approaches suffer from lowh ydroxylation efficiencya nd specificity or low protein yields. [17] Residue-specific replacement [18,19] of Tyrb yD OPA, exploiting the substrate promiscuityo fEscherichia coli tyrosyl-tRNA synthetase (EcTyrRS), has been reported for MAP types 3a nd 5, [17] but is limited by the poor activation of DOPAb yEcTyrRS, accompanied by Tyr incorporation ( Figure S1 in the Supporting Information), and impaired cell growth due to proteome-wide DOPAi ncorporation.…”
mentioning
confidence: 99%
“…The in vivo residue‐specific Dopa incorporation allowed for a high incorporation yield, around 90%, which is close to the yields of natural MAPs, and allowed Dopa to stay in its reduced form (Yang et al, 2014); moreover, d MAPs produced by this method showed superior underwater adhesion ability, similar to natural MAPs (Yang et al, 2014). However, potential use of these high‐quality d MAPs as practical bioglues was hindered by their low production yield, 3–5 mg/L (Yang et al, 2014). Therefore, there is a pressing need for increasing productivity toward commercialization.…”
Section: Introductionmentioning
confidence: 93%
“…Because of this, there have been many attempts to effectively incorporate Dopa into E. coli ‐derived MAPs (Choi, Yang, Yang, & Cha, 2012; Lim et al, 2011). To date, in vivo residue‐specific Dopa incorporation is known as the most efficient method of incorporating Dopa into E. coli ‐derived MAPs, via mis‐aminoacylation of Dopa by endogenous tyrosyl‐tRNA synthetase (TyrRS) in a tyrosine‐auxotrophic strain under minimal conditions (Yang et al, 2014). Conventional methods involving in vitro mushroom‐tyrosinase modification showed a low modification yield of less than 15% (Yang et al, 2013, 2014), and in vivo modification via tyrosinase coexpression showed high instability between reduced and oxidized forms of Dopa, as tyrosinase can also catalyze oxidization of Dopa to Dopa‐quinone (Choi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations